Trusting the trustless blockchain for its adoption in accounting: theorizing the mediating role of technology-organization-environment framework - Sujata Seshadrinathan; Shalini Chandra (Financial Innovation)
Abstract Blockchain technology has a unique ability to automate accounting processes that are a part of regulatory requirements in all commercial enterprises. Moreover, it can hold verified accounting records and eliminate the need for a trusted third party. Despite blockchain's potential to transform the nature of traditional accountancy procedures, adoption by the accounting industry is somewhat limited. Knowledge in this domain is lacking, and research on the antecedents influencing the adoption of blockchain-based accounting systems is scarce. This study is rooted in the technology-organization-environment (TOE) framework, presenting a trust-centric adoption model based on diligent analysis of blockchain and technology adoption literature. The model proposes that TOE factors mediate trust's role in adopting blockchain for accounting applications. The model was validated based on qualitative semi-structured interviews of twelve industry leaders and was comprehensively tested using a quantitative survey-based methodology with accounting professionals knowledgeable about blockchain technology. The data collected was analyzed using PLS-SEM. The results demonstrate the role of trust and the mediating effect of the theorized TOE variables on adopting blockchain-based accounting solutions. The results' implications for research and practice are discussed.